'We do what we can as soon as we can' Alcohol and Other Drug workforce perspectives on preventing and responding to prenatal alcohol exposure. (2nd November 2021) - Pedruzzi, Rebecca A.; Hamilton, Olivia; Hodgson, Helena H. A.; Connor, Elizabeth; Johnson, Elvira; Fitzpatrick, James
Abstract: Evidence based strategies are needed to enhance the ability of the Alcohol and Other Drugs (AOD) sector to prevent prenatal alcohol exposure (PAE) and harms including Fetal Alcohol Spectrum Disorder (FASD). In Australia FASD prevention research has largely focused on primary care and child development sectors, while little research has been conducted with AOD services providing comprehensive support to high risk women. This study interviewed 26 staff from 18 organizations involved in referral and co-ordination, case management, or treatment and support services for women with (or at high risk of) PAE in the Greater Newcastle region in Australia. Interviews with service workers indicated a significant appreciation of the psychosocial complexities related to substance misuse in pregnancy, a highly skilled approach to harm reduction, and a sector going to extraordinary lengths to overcome the disadvantages faced by women including gaps in service provision. These results are discussed in light of recommendations to support AOD services to reduce the harms of PAE.